Demystifying Parallel Build Methodologies in Product Lifecycle Management : A Foundational Overview - Pradeep Karanam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Parallel build methodologies are transforming Product Lifecycle Management by enabling simultaneous development of multiple product revisions, particularly in fast-paced industries like consumer electronics and AR/VR hardware. This overview explores how parallel approaches overcome traditional sequential bottlenecks, including time lags, revision conflicts, and limited iteration capacity. By implementing core principles like dynamic assembly labeling, non-destructive concurrent work, and selective inheritance, organizations gain significant advantages. The article examines enabling technologies, including data model adaptations and workflow orchestration systems, while detailing implementation best practices across data modeling, process governance, and software customization. Benefits include accelerated development timelines, improved cross-functional collaboration, and enhanced responsiveness to market changes—critical advantages in competitive technology markets where time-to-market pressures continue to intensify.
Keywords: Parallel Development; Product Lifecycle Management; Concurrent Engineering; Change Propagation; Cross-Functional Collaboration